Biomechanical comparison of conventional and optimised locking plates for the fixation of intraarticular calcaneal fractures: a finite element analysis. Issue 12 (10th September 2017) - Ouyang, Hanbin; Deng, Yuping; Xie, Pusheng; Yang, Yang; Jiang, Bingyun; Zeng, Canjun; Huang, Wenhua
Abstract: Intraarticular calcaneal fractures can result in poor prognosis. Although operative fixation can improve the functional outcomes in most cases, surgical complications such as loss of reduction and wound healing problems may increase the risk of reoperation. Hence, this study aimed to design calcaneal locking plate with a lower profile and better biomechanical performance   and to compare the redesigned plate with the traditional calcaneal plate via the finite element method. A Sanders' type II-C intraarticular calcaneal fracture was simulated. Two fixation models utilising the branch-like calcaneal locking plate and the full plate were constructed. Topology optimisation was conducted to generate a new calcaneal plate design. A biomechanical comparison among the three groups of plates was performed using the finite element method. For the fracture simulated in this study, the optimised plate was superior to the traditional plate in terms of fixation stability and safety but was reduced in volume by approximately 12.34%. In addition, more rational stress distributions were observed in the redesigned plate, underscoring the superiority of this new design in terms of fatigue strength. These results demonstrate that the topology optimisation can be used to design a new implant with a minimised profile and no loss of fixation stability.